Youth Mentor Dietary Outcomes and Waist Circumference Improvement: Camp NERF Study Findings. Issue 6 (November 2020) - Hopkins, Laura C.; Webster, Alison; Kennel, Julie A.; Purtell, Kelly M.; Gunther, Carolyn
Background . The health impact of youth mentors serving in the delivery of child nutrition and physical activity (PA) interventions on youth mentors themselves has been understudied. Objective . The primary objective of the current study was to examine the impact of engaging youth mentors in the delivery of a summertime childhood obesity prevention intervention on youth mentors' behavioral health. Method . Data were collected at baseline and postintervention. A survey of validated nutrition, mental health, PA, and psychosocial questionnaires was administered. Diet was assessed via 24-hour recall. Height, weight, and waist circumference (WC) were measured. In-depth interviews were conducted with youth mentors. Results . Eleven youth mentors enrolled: 60% were female, mean age was 16.1 ± 0.38 years, and 100% were Black. Mean kilocalories ( p = .05), sugar-sweetened beverage intake ( p = .08), and waist circumference ( p = .04) decreased. In-depth interviews were conducted with 11 youth mentors, and three themes emerged: perceived improvement in nutrition, PA, and mental health-related behaviors; formation of a positive role modeling relationship with the child campers; and strengthening of higher education goals and future career aspirations. Conclusions . Youth mentor staffing may be an important intervention strategy for changing health behaviors among youth mentors. Results from this study can be used to inform utilization of youth mentors in the delivery of this and similar health behavior interventions in the future.